Mudharabah And Musyarakah Financing On Profitability Of Islamic Banking: A Literature Review - Syamsuarni Syamsuarni; Nurfitriani Nurfitriani; Indah Anggraeni Bachtiar; Syaripuddin Syaripuddin (Al-Hilali: Jurnal Perbankan dan Ekonomi Islam, 2026)
This study aims to analyze and synthesize the influence of Mudharabah and Musyarakah financing on the profitability of Islamic banks, particularly PT. Bank Syariah Indonesia (BSI), through a systematic literature review approach. The phenomenon of fluctuating Mudharabah financing and continuously increasing Musyarakah financing at BSI during the period 2021–2025 raises important academic questions regarding their respective contributions to profitability measured by Return on Assets (ROA). This study employs a qualitative research method with a literature review approach, systematically collecting, analyzing, and synthesizing relevant academic sources including journals, theses, and books published in the last ten years. The results of the literature synthesis show that: (1) Mudharabah financing tends to have a negative and non-significant effect on profitability due to high uncertainty, moral hazard risks, and weak supervision of partner business activities; (2) Musyarakah financing consistently shows a positive and significant influence on profitability because of its lower risk nature, active bank involvement in business management, and proportional profit-sharing mechanism; (3) simultaneously, Mudharabah and Musyarakah financing together contribute significantly to BSI profitability, with the dominant role played by Musyarakah. These findings are in line with various empirical studies and provide theoretical and practical implications for Islamic banking institutions, regulators, and future researchers in the development of Islamic banking financing strategies.